Temporal patterns of lipoperoxidation and antioxidant enzymes are modified in the hippocampus of vitamin A-deficient rats - Navigatore Fonzo, Lorena Silvina (2009)
Animals can adapt their behavior to predictable temporal fluctuations in the environment through both, memory-and-learning processes and an endogenous time-keeping mechanism. Hippocampus plays a key role in memory and learning and is especially susceptible to oxidative stress. In compensation, antioxidant enzymes activity, such as Catalase (CAT) and Glutathione peroxidase (GPx), has been detected in this brain region. Daily rhythms of antioxidant enzymes activity, as well as of glutathione and lipid peroxides levels, have been described in brain. Here, we investigate day/night variations in lipoperoxidation, CAT, and GPx expression and activity, as well as the temporal fluctuations of two key components of the endogenous clock, BMAL1 and PER1, in the rat hippocampus and evaluate to which extent vitamin A deficiency may affect their amplitude or phase. Holtzman male rats from control, vitamin A-deficient, and vitamin A-refed groups were sacrificed throughout a 24-h period. Daily levels of clock proteins, lipoperoxidation, CAT and GPx mRNA, protein, and activity, were determined in the rat hippocampus obtained every 4 or 5 h. Gene expression of RARα and RXRβ was also quantified in the hippocampus of the three groups of rats. Our results show significant daily variations of BMAL1 and PER1 protein expression. Rhythmic lipoperoxidation, CAT, and GPx, expression and activity, were also observed in the rat hippocampus. Vitamin A deficiency reduced RXRβ mRNA level, as well as the amplitude of BMAL1 and PER1 daily oscillation, phase-shifted the daily peak of lipoperoxidation, and had a differential effect on the oscillating CAT and GPx mRNA, protein, and activity. Learning how vitamin A deficiency affects the circadian gene expression in the hippocampus may have an impact on the neurobiology, nutritional and chronobiology fields, emphasizing for the first time the importance of nutritional factors, such as dietary micronutrients, in the regulation of circadian parameters in this brain memory-and-learning-related region.